(untitled) (Research, Society and Development, 2021)
The objective of this work was to investigate the knowledge of the community of Sítio Pinheira in the municipality of Missão Velha-CE about medicinal plants, as well as the part used and the form of use. Semi-structured interviews were conducted with residents ranging in age from 60 to 88 years, corresponding to 44 people of both sexes. The questions were based on personal issues and ethnobotanical knowledge. The species were identified through photographic records made at the time of the interviews, the photographs being compared with specialized bibliography and the scientific names confirmed in the Flora do Brasil 2020 virtual database. A total of 148 medicinal species were obtained, distributed in 65 families botanical, with greater emphasis on Asteraceae, Fabaceae and Lamiaceae. As the most used part, the sheet was obtained as 40% of the answers, the most used form for the treatment was the decoction method with 36% of the citations. The most referred diseases were those related to the respiratory system and the digestive system. It is concluded that the community makes a great use of medicinal plants and that it can be considered a traditional community.